Optimization of the Number of Boat Passengers Using the Intact Stability Survival Approach - Aditya Dwi Saputra; Sjarief Widjaja; Hasanudin (International Journal of Marine Engineering Innovation and Research, 2025)
Passenger ship accidents in Indonesia’s domestic waters are frequently linked to overloading and stability failures, particularly on non-classed vessels with open decks. This study proposes an analytical method to determine the optimal passenger capacity based on intact stability survival criteria. The method begins with hydrostatic calculations of the hull to generate the KN curve, which is then adjusted for the mass distribution of the vessel and passengers to produce the actual GZ curve. Optimization is performed iteratively by comparing the calculated righting moment (Mst) with the regulatory criterion moment (Mkr), following both BKI and ISO 12217-1:2015 standards, while also accounting for the limiting condition at the downflooding angle. A case study on a V-hull boat (L = 10.5 m; B = 3.2 m; H = 1.4 m) reveals a substantial divergence between the two regulatory frameworks. Under light displacement (LWT = 1 ton), ISO permits up to 138 passengers, whereas BKI limits capacity to only 17. Conversely, at a high LWT of 8 tons, ISO does not allow any passengers, while BKI still permits approximately 29. Validation against Maxsurf software demonstrates excellent agreement (R² = 0.9993), confirming the reliability of the developed program. These findings establish that the proposed method is both valid and practical, offering a technical guideline for determining the safe passenger capacity of non-classed open-deck vessels operating in domestic waters.